Corona und andere Weltuntergänge: Apokalyptische Krisenhermeneutik in der modernen Gesellschaft - Nagel, Alexander-Kenneth (Kulturen der Gesellschaft, 2021)
Financial crisis, refugee crisis, climate emergency and now Corona. The 21st century has been rich in crises from the very beginning. At the same time, apocalyptic interpretations of world events have been popular since the turn of the millennium at the latest. Alexander-Kenneth Nagel analyzes the apocalyptic deep structure of current crisis diagnoses on the Corona pandemic, the ecological crisis from the Club of Rome to Extinction Rebellion and the crisis of nationalism. He provides a deeper understanding of the end-time mentality of late modern societies and the ongoing boom in apocalypticism as a religious and ideological business model